Remission of social behavior impairment by oral administration of a precursor of NAD in CD157, but not in CD38, knockout mice - Gerasimenko, Maria; Higashida, Haruhiro (Frontiers in Immunology, 2023)
• Nicotinamide adenine dinucleotide (NAD) is a substrate of adenosine diphosphate (ADP)-ribosyl cyclase and is catalyzed to cyclic ADP-ribose (cADPR) by CD38 and/or CD157. cADPR, a Ca2+ mobilizing second messenger, is critical in releasing oxytocin from the hypothalamus into the brain. Although NAD precursors effectively play a role in neurodegenerative disorders, muscular dystrophy, and senescence, the beneficial effecta of elevating NAD by NAD precursor supplementation on brain function, especially social interaction, and whether CD38 is required in this response, has not been intensly studied. Here, we report that oral gavage administration of nicotinamide riboside, a perspective NAD precursor with high bioavailability, for 12 days did not show any suppressive or increasing effects on sociability (mouse’s interest in social targets compared to non-social targets) in both CD157KO and CD38KO male mice models in a three-chamber test. CD157KO and CD38KO mice displayed no social preference (that is, more interest towards a novel mouse than a familiar one) behavior. This defect was rescued after oral gavage administration of nicotinamide riboside for 12 days in CD157KO mice, but not in CD38KO mice. Social memory was not observed in CD157KO and CD38KO mice; subsequently, nicotinamide riboside administration had no effect on social memory. Together with the results that nicotinamide riboside had essentially no or little effect on body weight during treatment in CD157KO mice, nicotinamide riboside is less harmful and has beneficial effect on defects in recovery from social behavioral, for which CD38 is required in mice.